Band Structure and optical properties of CDSE compounds calculated using density functional theory (DFT-LDA) and (DFT-GGA) - Azhaar Jalal Brakhas (Genius Journals, 2022)
This work studies the band structure and optical properties of Cadmium selenide (CdSe)are calculated by using density functional theory (DFT) on the implemented in CASTEPcod
Keywords: Castep code; DFT (LAD); DFT (GGA)